GASTRO-INTESTINAL PARASITES IN WILD CARNIVORES OF WESTERN GHATS OF TAMIL NADU - R.A. Valarmathi; B. Nishanth; C. Sreekumar; P. Azhahianambi; M.G. Ganesan (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Western Ghats is a hotspot of biodiversity with different species of carnivores. The gastrointestinal parasites prevailing among free-ranging carnivores were documented by examination of forty-three (N=43) faecal samples collected in selected regions of Western ghats by perambulation from February to September, he study revealed an overall percentage of endoparasitic infection of about 60.46% (n=26). The percentage of infection of gastrointestinal parasites in tiger (n=13), leopard (n=17), dhole (n=8) and golden jackal (n=5) were 38.46%, 76.47%, 75.00% and 40.00% respectively. Toxocara spp. and Taenia sp. were documented in all four carnivore species, whereas Diphyllobothrium sp. eggs were recorded only in leopards. Trichuris sp.and Sarcocystis sporocyst were detected only in tiger samples. Strongyle eggs were recorded only in leopards and dholes.